EU Civilian Crisis Management and Organisational Learning - Raphael Bossong (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Commentators and policy-makers stress the need to learn the lessons of EU civilian crisis management. Yet despite numerous case studies mission performance, we know little about the EU's overall capacity for such learning. The first part of this article outlines a theoretical framework for analysing organisational learning in the context of peace operations. It recommends focusing on administrative reform and conceptual development in Brussels, and lists various factors that are expected to facilitate or inhibit organisational learning cycles. On this basis, second part presents a historical survey of the EU's learning efforts in civilian crisis management. Despite a dynamic expansion of mission tasks as well as corresponding review processes, organisational learning has remained haphazard and limited to capacity expansion or mission support requirements. Only over the last two years did the EU invest in more formalised lessons-learning processes, which led to improved information gathering across missions and created more space for conceptual discussions on mission objectives. Yet at the time of writing, this increased institutional momentum for learning could not overcome fundamental political constraints on more ambitious reforms of EU peace operations.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330